So you want to find
Integral (x (3 - x)^(1/2) dx)
One of the ways you can do this is through substitution, but used in a slightly nonconventional method. Normally during U substitution, you immediately solve for du; here, we're going to take a few steps prior to solving for du.
Let u = 3 - x. Then, moving the -x to the left hand side and moving the u to the right hand side,
x = 3 - u
Differentiating, we get
dx = -du
And now we substitute accordingly and get
Integral [(3 - u) [u]^(1/2) (-du) ]
It's always a good idea to pull out constants; in this case, we can pull out the (-1) in front of that du, to obtain,
(-1) * Integral [ (3 - u)u^(1/2) du]
Now, let's distribute that u^(1/2) over the brackets, to obtain
(-1) * Integral [ (3u^(1/2) - u*u^(1/2) du ]
Note that u is the same as u^(1), and u^(1/2) is multiplied to it. That means we're multiplying two things with the same base but different exponent; when we do this, we add the exponents, so
u*u^(1/2) = u^(1 + 1/2) = u^(3/2). Thus, we get
(-1) * Integral [ (3u^(1/2) - u^(3/2) du ]
Now, we integrate normally using the power rule.
(-1) * [ 3 (2/3)u^(3/2) - (2/5) u^(5/2) ] + C
Let's clean this up a bit, to obtain,
(-1) * [ u^(3/2) - (2/5) u^(5/2) ] + C
And note the impact of that (-1) on the outside; that's just going to reverse the terms, while keeping it a difference of terms.
(2/5) u^(5/2) - u^(3/2) + C
Now we replace u = 3 - x.
(2/5) (3 - x)^(5/2) - (3 - x)^(3/2) + C
2007-01-15 11:13:18
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Let u = x and dv/dx = (3-x)^(1/2)
So du/dx = 1 and v = (-2/3)*(3-x)^(3/2)
Since
Integral of (u)(dv/dx) dx = uv - integral of (v)(du/dx) dx
Integral of x* (3-x)^(1/2)
= (2x/3)*(3-x)^(3/2) - integral of (-2/3)*(3-x)^(3/2) dx + C
= (2x/3)*(3-x)^(3/2) - (-2/5)(-2/3)*(3-x)^(5/2) + C
= (2x/3)*(3-x)^(3/2) - (4/15)*(3-x)^5/2 + C
2007-01-15 15:34:07
·
answer #2
·
answered by Kemmy 6
·
0⤊
0⤋